Hb S-β-thalassemia: molecular, hematological and clinical comparisons - Serjeant, Graham R.; Serjeant, Beryl E.; Fraser, Raphael A.; Hambleton, Ian R.; Higgs, Douglas R.; Kulozik, Andreas; Donaldson, Alan (Hemoglobin, 2011)
Clinical and hematological features are presented for 261 patients with identified β-thalassemia (β-thal) mutations. Mutations causing Hb S [β6(A3)Glu→Val]-β0-thal were IVS-II-849 (A>G) in 44%, frameshift codon (FSC) 6 (-A) in 14%, Hb Monroe [β30(B12)Arg→Thr] in 14%, and IVS-II-1 (G>A) in 10%. Mutations causing Hb S-β+-thal with 14-25% Hb A (type III) were -29 (A>G) mutation in 60%, -88 (C>T) in 22% and the polyadenylation signal site (polyA) (T>C) mutation in 14%, and in Hb S-β+-thal with 1-7% Hb A (type I), all had the IVS-I-5 (G>C) mutation. Hematologically, only minor differences occurred between the four Hb S-β0-thal mutations, but among the three mutations causing Hb S-β+-thal type III, levels of Hb A2, Hb F, hemoglobin (Hb), MCV and MCH were highest in the -88 and lowest in the polyA mutations. Clinically, Hb S-β0-thal and Hb S-β+-thal type I were generally severe, and Hb S-β+-thal type III disease with the -88 mutation was milder than that caused by the polyA mutation.
Gesehen am 23.11.2022